An Improved Optical Fiber Remote Sensing Method Based on Polarized Low-Coherence Interferometry - Kun Liu; Dongdong Ju; Shuang Wang; Junfeng Jiang; Mengnan Xiao; Xue Wang; Tiegen Liu (IEEE Photonics Journal, 2018)
We proposed an improved phase-based method by using a filtering window on the low-coherence interferogram. Through theoretical derivation and numerical simulation, we prove the correction of our proposed method that the fringe phase can be demodulated nondestructively after applying a symmetrical filtering window nearby the envelope peak, and our method can enhance system SNR. Since fringe overlap phenomenon arising from narrow bandwidth occurs frequently in single-mode sensing system, this method is especially applicable to remote sensing wherein the localization of interference fringe is difficult using traditional phase-based methods. To verify this method, an experiment with a single-mode fiber Fabry-Perot air pressure sensing system was carried out. The experiment results showed that the precision using our method decreased to less than 0.053 $%$ in full 280 kPa pressure scale and the sensing distance extended to 20 km, which were apparently superior to traditional phase-based methods.